The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2012
DOI: 10.1038/nature11220
|View full text |Cite
|
Sign up to set email alerts
|

Biophysical mechanism of T-cell receptor triggering in a reconstituted system

Abstract: A T cell-mediated immune response is initiated by the T cell receptor (TCR) interacting with peptide-bound MHC (pMHC) on an infected cell. The mechanism by which this interaction triggers intracellular phosphorylation of the TCR, which lacks a kinase domain, remains poorly understood. Here, we have introduced the TCR and associated signalling molecules into a nonimmune cell and reconstituted ligand-specific signalling when these cells are conjugated with antigen presenting cells. We show that signalling requir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

20
327
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 305 publications
(353 citation statements)
references
References 38 publications
20
327
1
1
Order By: Relevance
“…Notably, in addition to the conformational dynamics model shown here, other models such as kinetic segregation and kinase regulation have been shown to be crucial in TCR activation [7,8,76,77]. Our finding does not contradict other models but rather support the notion that different factors act together to generate a multi-layered regulation of TCR activation.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Notably, in addition to the conformational dynamics model shown here, other models such as kinetic segregation and kinase regulation have been shown to be crucial in TCR activation [7,8,76,77]. Our finding does not contradict other models but rather support the notion that different factors act together to generate a multi-layered regulation of TCR activation.…”
Section: Discussionsupporting
confidence: 75%
“…The kinase-phosphatase equilibrium should play a key role in Step 2 in regulating ITAM phosphorylation. Kinetic segregation of phosphatases and the local enrichment of active Lck are both important to initiate TCR phosphorylation [7,8,76,77]. Altogether, the initial TCR triggering is regulated by a complex mechanism and modulation of either lipid binding-dissociation equilibrium or kinase-phosphatase equilibrium can affect the final outcome of TCR activation.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between the immune synapse gap and the efficiency of T-cell activation and cytoIysis is well documented. 21 Consistent with these observations, it has been reported that the size of the extracellular domain of antigens targeted by BiTEs influences the efficacy of the cell killing, such that molecules with large extracellular domains do not lead to efficient redirected cell lysis. 22 In a similar way, it could be hypothesized that the size of the bispecific molecules could affect the potency of the cell killing, with larger molecules being less efficient than smaller molecules.…”
Section: Discussionsupporting
confidence: 52%
“…These data suggest that the hRSV N may inhibit IS assembly via mechanisms that take advantage of the low affinity of the physiological TCR−pMHC interaction. For example, N may (i) impair bending of the T-cell membrane necessary to form a close contact (44), or (ii) impair physiological microclustering of newly formed monovalent pMHC−TCR pairs.…”
Section: Resultsmentioning
confidence: 99%